Tinjauan Hukum Internasional Terhadap Konflik Batas Maritim Zona Ekonomi Eksklusif (Zee) Antara Indonesia Dan Vietnam = Review Of International Law On The Exclusive Economic - Alia Fahlika Sari; Rendy Agung Kurniawan; Nana Ervina (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The maritime boundary dispute in the Exclusive Economic Zone (EEZ) between Indonesia and Vietnam is a complex issue under international law of the sea. Differing interpretations of the boundary line and competing economic interests, particularly regarding fishery resources, are the primary factors driving this conflict. This study aims to analyze the EEZ dispute between Indonesia and Vietnam through the lens of international law, specifically based on the provisions of the 1982 United Nations Convention on the Law of the Sea (UNCLOS). The method used is normative legal research employing a statutory approach and a literature review. The results of the study indicate that the resolution of maritime boundary disputes must prioritize the principles of justice, equality, and peaceful settlement as stipulated in UNCLOS 1982. Indonesia and Vietnam have essentially undertaken various diplomatic efforts, including bilateral negotiations, to reach an agreement on the delimitation of EEZ boundaries. From an international law perspective, these steps align with states’ obligations to avoid armed conflict and prioritize peaceful resolution. Therefore, sustained commitment from both countries is necessary to strengthen cooperation and ensure legal certainty in the disputed maritime area.